COVID-19 infection risk amongst 14, 104 vaccinated care home residents: a national observational longitudinal cohort study in Wales, UK, December 2020–March 2021. (17th November 2021) - Hollinghurst, Joe; North, Laura; Perry, Malorie; Akbari, Ashley; Gravenor, Mike B; Lyons, Ronan A; Fry, Richard
Abstract: Background: vaccinations for COVID-19 have been prioritised for older people living in care homes. However, vaccination trials included limited numbers of older people. Aim: we aimed to study infection rates of SARS-CoV-2 for older care home residents following vaccination and identify factors associated with increased risk of infection. Study Design and Setting: we conducted an observational data-linkage study including 14, 104 vaccinated older care home residents in Wales (UK) using anonymised electronic health records and administrative data. Methods: we used Cox proportional hazards models to estimate hazard ratios (HRs) for the risk of testing positive for SARS-CoV-2 infection following vaccination, after landmark times of either 7 or 21 days post-vaccination. We adjusted HRs for age, sex, frailty, prior SARS-CoV-2 infections and vaccination type. Results: we observed a small proportion of care home residents with positive polymerase chain reaction (tests following vaccination 1.05% (N = 148), with 90% of infections occurring within 28 days. For the 7-day landmark analysis we found a reduced risk of SARS-CoV-2 infection for vaccinated individuals who had a previous infection; HR (95% confidence interval) 0.54 (0.30, 0.95). For the 21-day landmark analysis, we observed high HRs for individuals with low and intermediate frailty compared with those without; 4.59 (1.23, 17.12) and 4.85 (1.68, 14.04), respectively. Conclusions: increased risk of infection after 21 days was associated with frailty. We found most infections occurred within 28 days of vaccination, suggesting extra precautions to reduce transmission risk should be taken in this time frame.